Colorimetric and Fluorescence Dual-Mode Biosensors Based on Peroxidase-Like Activity of the Co3O4 Nanosheets - Tan, Jingying; Geng, Weifu; Li, Junde; Wang, Zhen; Zhu, Shaohao; Wang, Xiuzhong (Frontiers in Chemistry, 2022)
Mimic enzyme has become a research hotspot in recent years because of its advantages of high stability, convenient preparation and low price. In this paper, Co3O4 nanosheets synthesized by simple hydrothermal method has the characteristics of peroxidase-like activity. The results demonstrated that 3,3′,5,5′-tetramethylbenzidine (TMB) could be oxidized by H2O2 to produce a typical blue product (oxTMB) which has strong absorption at 650 nm wavelength with the help of Co3O4 nanosheets. Thus, a simple and sensitive colorimetric detection method for H2O2 was established with a good linear relationship (2 – 200 μM) and a low detection limit of 0.4 μM. Meanwhile, the colorimetric product can effectively quench the fluorescence emitted by Ru(bpy)32+. Therefore, a colorimetric and fluorescence dual detection modes photochemical sensor for H2O2 detection is constructed based on the principle of inner filter effect (IFE) between colorimetric product (oxTMB) and Ru(bpy)32+. It can effectively avoid the false positive problem of single detection mode. Glucose can be catalyzed to produce gluconic acid and H2O2 in the presence of glucose oxidase, therefore, the sensor can also be used for the determination of glucose with a good linear relationship (0.02 – 2 μM) and a low detection limit of 5 nM. Experimental results showed that the sensor has high sensitivity and strong anti-interference ability which can be used for the detection of actual samples.